EFFECTIVENESS OF MUSIC THERAPY ON SELECTED EFFECTS OF CHEMOTHERAPY PATIENTS - MS. DIVYA UPRETI, PROF. DR. PITY KOUL (TPM – Testing, Psychometrics, Methodology in Applied Psychology, 2025)
Introduction: The World Cancer Research Fund emphasised that most cancers is the main reason of lack of lifestyles worldwide, with 7.6 million of her deaths in 2008 (approximately 13% of all deaths). By 2030, the number of cancer cases is projected to exceed 11 million. Aim: The Objective of study is to determine the effectiveness of music therapy on selected side effects of chemotherapy among cancer patients and to find the association of demographic variables with selected side effects of chemotherapy among cancer patients in the experimental group and the control group. Material and Methods: three parallel arm RCT with SNOSE randomisation was done and with eight patients assessed to identify the selected side effects experienced by cancer patients, which include nausea, vomiting and lack of sleep , across three chemotherapy sessions. The Multinational Association of Supportive Care in Cancer (MASCC) was utilized to assess nausea and vomiting, while the Pittsburgh Sleep Quality Index scale was employed to evaluate sleep quality. The participants were divided into two groups, each consisting of four patients each. The experimental group received music therapy for 30 minutes each day, whereas the control group was provided with standard treatment care for three consecutive chemotherapy sessions.. Result shows a significant association seen between patients performing Music therapy. Results showed that the group receiving MT had a reduction in chemotherapy side effects compared with control group. Conclusion: The study concluded that music therapy was more effective in controlling the side effects of chemotherapy among cancer patients. Positive difference in the selected side effects of chemotherapy among cancer patients before and after the administration of music therapy in the experimental group.